The Vegetable Kingdom Or, the Structure, Classification, and Uses of Plants Illustrated upon the Natural System - Lindley, John 1799-1865 (Cambridge University Press, 1847)
Employed early in his career by Sir Joseph Banks, the botanist John Lindley (1799–1865) is best known for his recommendation that Kew Gardens should become a national botanical institution, and for saving the Royal Horticultural Society from financial disaster. As an author, he is best remembered for his various works on taxonomy and classification. This work, one of his most famous, was first published in 1846; reissued here is the revised third edition of 1847. Lindley describes his motive as being 'to make his countrymen acquainted with the progress of Systematic Botany abroad' given that the 'superficial and useless system of Linnaeus' was now consigned to history. The work, nonetheless an important milestone in the development of plant taxonomy, gives an overview of the various classification systems used since that of John Ray, and goes on to define the vegetable kingdom in terms of classes and 'alliances' of plants
Includes index. - Originally published in 1847
Keywords: Plants / Classification; Plants, Useful; Plant anatomy